Can We Increase the Value and Decrease the Cost of Clinical Skills Assessment?. (May 2018) - Burdick, William P.; Boulet, John R.; LeBlanc, Kim Edward
Abstract : Although the authors do not agree with medical students' bid to end the United States Medical Licensing Examination Step 2 Clinical Skills or Comprehensive Osteopathic Medical Licensing Examination Level 2-Performance Evaluation tests, they concur with Ecker and colleagues that conducting further research to support the validity argument, providing greater feedback on performance, and exploring options to reduce costs are important for addressing students' concerns. Evidence to support the validity of clinical skills exam scores and associated inferences already exists. What is lacking, and would help further justify the use of these examinations, is more evidence to support the "extrapolation" argument—that is, is performance on these examinations related to actual patient care? Enhanced feedback on exam performance should also be considered. While performance data from licensing examinations should be used judiciously given the primary purpose of these tests, additional data would be helpful to learners and their institutions. Centralized testing remains the least costly design, but efficiencies of standardized patient training, case development, and scoring can be reviewed. Scoring modifications made in the past several years at substantial cost should be evaluated to determine whether they have achieved desired goals. Testing organizations can and should embrace these essential elements of transparency and accountability to address concerns about the value of clinical skills examinations.